Empowering Women Through Innovation In Processing Fishery By-Products Assisted By PT Pertamina Patra Niaga IT Makassar - Andi Ade Ula Saswini; Sandy Pramudikta; Muh Haris; Dwi Wijayanto; Rini Jusriani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The proliferation of businesses in the culinary sector and the increasing number of processed fishery products simultaneously increase the burden of organic waste resulting from community business activities in the Pattingalloang sub-district. One of the efforts made is need to develop Micro, Small, Medium Enterprises (MSMEs ) that are able to manage fishery by-products into products with high selling value and high nutrition. This activity was carried out in the Pattingalloang sub-district involving the Srikandi Group assisted by PT Pertamina Patra Niaga IT Makassar. The method used was to provide product making training for women who are members of The Srikandi Group which was then carried out pre and post tests, apart from that, proximate testing was also carried out to ensure that The resulting products have good quality and nutritional content. The results of this activity were able to increase mothers' knowledge regarding the management of fishery by-products and produce fried meatball products from shrimp shells with a calcium content of 679.35 µg/g per 100 grams.